The Effect of Capital Adequacy and Bank Size on Non-Performing Loans in Indonesian Public Banks - Eka Yulianti; Aliamin Aliamin; Ridwan Ibrahim (Universitas Syiah Kuala, 2018)
AbstractObjective – This study aims to analyze the effect of capital adequacy and bank size on nonperforming loans in public banks in Indonesia for the 2012-2016 period. Design/methodology – The secondary data used is obtained from the Financial Statements published by Bank Indonesia. This research is a hypothesis-testing study. Purposive sampling method was utilized and 81 samples constitute the final samples of this study. Multiple linear regression analysis with panel data estimation was run to test the hypotheses. Results – The results show that simultaneously capital adequacy ratio, bank size, and loan to deposit ratio have an effect on nonperforming loans. Partially, the result shows that capital adequacy ratio has a positive effect on non-performing loans, while bank size negatively affects nonperforming loans, and loan to deposit ratio negatively affects nonperforming loans. Research limitations/implications – This study is perhaps limited in the number of variables used to test the model. There may be other variables influencing NPL in public banks in Indonesia hence future studies may broaden the scope of this study.